2009
DOI: 10.1093/mutage/gep036
|View full text |Cite
|
Sign up to set email alerts
|

The DNA repair gene APE1 T1349G polymorphism and cancer risk: a meta-analysis of 27 case-control studies

Abstract: Published data regarding the association between the apurinic/apyrimidinic endonuclease 1 (APE1) T1349G (Asp148Glu) polymorphism and cancer risk show inconclusive results. To derive a more precise estimation of the relationship, we performed a meta-analysis of 27 published studies that included 12 432 cancer cases and 17 349 controls. We used odds ratios (ORs) and 95% confidence intervals (CIs) to evaluate the strength of the associations. The overall results suggested that the variant genotypes were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Studies published in other languages were not included, which may bias the results. Second, further evaluation was limited due to the lack of original data, because the interactions between gene-gene, geneenvironment, and even different polymorphic loci of the same gene may modulate cancer risk (Gu et al, 2009). Third, the numbers of published studies were not sufficiently large for a comprehensive analysis; consequently, this study may not have adequate power to detect the possible risk for Ku70 -1310C/G promoter polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published in other languages were not included, which may bias the results. Second, further evaluation was limited due to the lack of original data, because the interactions between gene-gene, geneenvironment, and even different polymorphic loci of the same gene may modulate cancer risk (Gu et al, 2009). Third, the numbers of published studies were not sufficiently large for a comprehensive analysis; consequently, this study may not have adequate power to detect the possible risk for Ku70 -1310C/G promoter polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio (OR) was used as the metric of choice. For each genetic comparison, the χ 2 -based Q statistic and I2 statistic were adopted to estimate the between-study heterogeneity for all suitable comparisons (Lau et al, 1997;Gu et al, 2009). We combined data using both fixed-(Mantel-Haenszel) and random-effects (DerSimonian and Laird) models.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively studied is the Asp148Glu; A meta-analysis of 12432 cases showed an increased risk of cancers, especially of colorectal cancer for this allele. Functional studies have shown that this variant may have altered endonuclease and DNA-binding activity and reduced ability to interact with other BER proteins (Gu et al, 2009) in order to form critical complexes for nucleotide excision/incorporation during the rectifying process. Besides its endonuclease activity, APE1 has been shown to stimulate the DNA binding activity of numerous transcription factors that are involved in cancer promotion and progression such as Fos, Jun, nuclear factor-κB and p53, thus is actively involved in redox regulation of oncoproteins (Kelley et al, 2010).…”
Section: Common Polymorphisms In Ber and Cancer Riskmentioning
confidence: 99%